2016
DOI: 10.1080/03008207.2016.1208655
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and epigenetic regulation in osteoarthritis

Abstract: Osteoarthritis (OA) was once defined as a non-inflammatory arthropathy, but it is now well-recognized that there is a major inflammatory component to this disease. In addition to synovial cells, articular chondrocytes and other cells of diarthrodial joints are also known to express inflammatory mediators. It has been proposed that targeting inflammation pathways could be a promising strategy to treat OA. There have been many reports of cross-talk between inflammation and epigenetic factors in cartilage. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
145
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(149 citation statements)
references
References 169 publications
2
145
0
2
Order By: Relevance
“…In physiological situations, there is a dynamic balance between ECM synthesis and degradation [11]. The roles of matrix metalloproteinases 13 (MMP13) and an 'aggrecanase' known as a disintegrin and metalloproteinase with thrombospondin motifs − 5 (ADAMTS5), in OA through the degradation of ECM are well established [12][13][14]. It is also clear that type X collagen (COL10A1) is a marker of fibrochondrocyte hypertrophy in meniscus [9,15], and CEBPβ contributes to the pathophysiological process of OA [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In physiological situations, there is a dynamic balance between ECM synthesis and degradation [11]. The roles of matrix metalloproteinases 13 (MMP13) and an 'aggrecanase' known as a disintegrin and metalloproteinase with thrombospondin motifs − 5 (ADAMTS5), in OA through the degradation of ECM are well established [12][13][14]. It is also clear that type X collagen (COL10A1) is a marker of fibrochondrocyte hypertrophy in meniscus [9,15], and CEBPβ contributes to the pathophysiological process of OA [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the expression of genes involved in the carbohydrate metabolism and extracellular matrix components were up-regulated. Moreover, chronic low-grade in ammation has also been found contributing to the development and progression of OA [47]. During OA progression, the entire synovial joints were involved in the in ammation process [48].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown the important role of in ammation in the pathophysiology of OA [17] . Inhibition of chondrocyte in ammation was a potential therapeutic strategy in OA [18] . In this study, we rst reported that the effects of Sch C on the IL-1β-induced in ammation and cartilage damage by inhibiting MAPK and NF-B signal pathway in SW1353 cells.…”
Section: Discussionmentioning
confidence: 99%